Unveiling low level viremia in chronic hepatitis B: challenges and new horizons - Wang, Bingqing; Zeng, Tian; Yin, Wen; Ren, Chengrui; Chen, Yuting; Qian, Liqin; Huang, Peng; Zhu, Chuanlong; Yue, Ming (Frontiers in Cellular and Infection Microbiology, 2025)
Low-level viremia (LLV) in chronic hepatitis B (CHB) represents a significant challenge and area of interest in current clinical management. While nucleos (t)ide analogs (NAs) have demonstrated substantial efficacy in suppressing hepatitis B virus (HBV) replication, the application of highly sensitive detection methods has revealed that some treated patients continue to exhibit persistent or intermittent low-level viremia (HBV DNA: 12–2000 IU/mL). The mechanisms underlying LLV involve a synergistic interplay between host immune response deficiencies and HBV covalently closed circular DNA (cccDNA) persistence. Furthermore, the complex regulation of LLV is influenced by metabolic-associated steatotic liver disease (MASLD). Limitations in the clearance of cccDNA by current antiviral regimens also contribute to this phenomenon. LLV may elevate the risk of liver fibrosis progression, hepatocellular carcinoma (HCC), and end-stage liver disease. Current management strategies emphasize optimizing antiviral regimens, such as switching to tenofovir alafenamide (TAF) or combining therapies with pegylated interferon-alpha (Peg-IFN-α). Enhanced dynamic monitoring, including high-sensitivity HBV DNA assays and quantitative hepatitis B surface antigen (HBsAg) measurements, is also crucial. Moreover, exploring combination therapies involving immunomodulation and hepatocyte regeneration is warranted. Further research should integrate multi-omics technologies with prospective cohort studies to elucidate the host-virus interaction network in LLV. This will allow for the validation of synergistic effects between metabolic interventionsand immunotherapy, thereby advancing personalized precision medicine. This review systematically synthesizes the epidemiological characteristics, pathogenesis, influencing factors, prognosis, and clinical management advancements of LLV, aiming to provide novel perspectives for optimizing therapeutic strategies and translational research.